1989
DOI: 10.1051/apido:19890503
|View full text |Cite
|
Sign up to set email alerts
|

Drones as sons of drones in Apis mellifera

Abstract: Summary — Homozygous cordovan queens (Apis mellifera carnica) were inseminated by dark (+) and by brown (cd) drones (A. m. carnica) and kept in colonies of dark Carniolan workers Sealed brood out of these colonies was transferred into an incubator until emergence. Among the offspring of 3 colonies, some dark drones were found. In a second experiment, the same queens were introduced into colonies consisting entirely of yellow Italian workers (A. m. ligustica). Again dark drones were found among the progen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…In addition to pheromones, the number of laying workers who develop depends on the protein balance in the colony: if there are a large number of larvae to be nourished, no laying workers develop, even if plenty of pollen and honey is available 1 Page and Erickson (1988) and Visscher (1989) reported that workers reproduce in small numbers during normal queenright conditions. However, Koeniger et al (1989) reported that the queen may produce drones who do not have the genome of this queen, but a genome that originated from the nucleus of a sperm. Drones may thus bear the genetic material of one of the males with whom the queen mated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to pheromones, the number of laying workers who develop depends on the protein balance in the colony: if there are a large number of larvae to be nourished, no laying workers develop, even if plenty of pollen and honey is available 1 Page and Erickson (1988) and Visscher (1989) reported that workers reproduce in small numbers during normal queenright conditions. However, Koeniger et al (1989) reported that the queen may produce drones who do not have the genome of this queen, but a genome that originated from the nucleus of a sperm. Drones may thus bear the genetic material of one of the males with whom the queen mated.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge there has been only one other report of clonal reproduction by males in the animal kingdom, in which it was found that 3 of 61 queens homozygous for a recessive (cordovan) mutation inducing a brown instead of the wild-type black colour produced some brown males 12 . This showed convincingly that some males could not originate from unfertilized eggs produced by queens, but it is possible that these males were diploid, as sometimes occurs in Hymenoptera 13 .…”
mentioning
confidence: 97%
“…Second, if a sperm cell fertilizes an anucleate egg, a sperm nucleus can potentially give rise to a clone of the sperm donor by ‘androgenesis’. Androgenesis is a well-established phenomenon in the honeybee Apis mellifera ( Koeniger et al 1989 ) and three ant species ( Fournier et al 2005 ; Kobayashi et al 2008 ; Pearcy et al 2004 ). In some ants a combination of androgenesis and thelytoky leads to the extraordinary situation in which queens clone themselves to produce daughter queens, and males clone themselves to produce sons ( Fournier et al 2005 ; Foucaud et al 2007 ).…”
mentioning
confidence: 99%